Gene Space and Transcriptome Assemblies of Leafy Spurge (Euphorbia esula) Identify Promoter Sequences, Repetitive Elements, High-Quality Markers, and a Full-Length Chloroplast Genome. Issue 3 (28th February 2018) - Horvath, David P.; Patel, Sagar; Doğramaci, Münevver; Chao, Wun S.; Anderson, James V.; Foley, Michael E.; Scheffler, Brian; Lazo, Gerard; Dorn, Kevin; Yan, Changhui; Childers, Anna; Schatz, Michel; et al.
Abstract: Leafy spurge ( Euphorbia esula L.) is an invasive perennial weed infesting range and recreational lands of North America. Previous research and omics projects with E. esula have helped develop it as a model for studying many aspects of perennial plant development and response to abiotic stress. However, the lack of an assembled genome for E. esula has limited the power of previous transcriptomics studies to identify functional promoter elements and transcription factor binding sites. An assembled genome for E. esula would enhance our understanding of signaling processes controlling plant development and responses to environmental stress and provide a better understanding of genetic factors impacting weediness traits, evolution, and herbicide resistance. A comprehensive transcriptome database would also assist in analyzing future RNA-seq studies and is needed to annotate and assess genomic sequence assemblies. Here, we assembled and annotated 56, 234 unigenes from an assembly of 589, 235 RNA-seq-derived contigs and a previously published Sanger-sequenced expressed sequence tag collection. The resulting data indicate that we now have sequence for >90% of the expressed E. esula protein-coding genes. We also assembled the gene space of E. esula by using a limited coverage (18X) genomic sequence database. In this study, the programs Velvet and Trinity produced the best gene-space assemblies based on representation of expressed and conserved eukaryotic genes. The results indicate that E. esula contains as much as 23% repetitive sequences, of which 11% are unique. Our sequence data were also sufficient for assembling a full chloroplast and partial mitochondrial genome. Further, marker analysis identified more than 150, 000 high-quality variants in our E. esula L-RNA–scaffolded, whole-genome, Trinity-assembled genome. Based on these results, E. esula appears to have limited heterozygosity. This study provides a blueprint for low-cost genomic assemblies in weed species and new resources for identifying conserved and novel promoter regions among coordinately expressed genes of E. esula .